2017
DOI: 10.1002/2016jd025940
|View full text |Cite
|
Sign up to set email alerts
|

Surface reflectivity climatologies from UV to NIR determined from Earth observations by GOME‐2 and SCIAMACHY

Abstract: The primary goal of this paper is to introduce two new surface reflectivity climatologies. The two databases contain the Lambertian‐equivalent reflectivity (LER) of the Earth's surface, and they are meant to support satellite retrieval of trace gases and of cloud and aerosol information. The surface LER databases are derived from the Global Ozone Monitoring Experiment (GOME)‐2 and Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) instruments and can be considered as improved and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(149 citation statements)
references
References 60 publications
2
147
0
Order By: Relevance
“…Surface reflectance at the lower accuracy sites in V2, such as at Chiba University, Kobe, Xinglong, and Osaka, is brighter (urban surfaces) than at other sites, and the current identification threshold of the darkest 1-3 % of observations, without considering surface type, results in climatologically derived values for reflectance that are too dark at bright (urbanized) surface sites. Tilstra et al (2017) suggested that selecting the mode of the RCR histogram improves the characterization of surface reflectance of bright surfaces compared with selecting the minimum values of the RCR. Choosing different thresholds for various surface types may improve the accuracy of retrievals over sites that have high surface reflectance.…”
Section: Regional Performancementioning
confidence: 99%
“…Surface reflectance at the lower accuracy sites in V2, such as at Chiba University, Kobe, Xinglong, and Osaka, is brighter (urban surfaces) than at other sites, and the current identification threshold of the darkest 1-3 % of observations, without considering surface type, results in climatologically derived values for reflectance that are too dark at bright (urbanized) surface sites. Tilstra et al (2017) suggested that selecting the mode of the RCR histogram improves the characterization of surface reflectance of bright surfaces compared with selecting the minimum values of the RCR. Choosing different thresholds for various surface types may improve the accuracy of retrievals over sites that have high surface reflectance.…”
Section: Regional Performancementioning
confidence: 99%
“…Meteorological information relevant to the retrieval are temperature-pressure profiles and surface pressure, acquired from the European Centre for Medium-Range Weather Forecast (ECMWF) ERA-Interim database (Dee et al, 2011) at the GOME-2A pixel using nearest-neighbour interpolation. Surface albedo is derived using nearest-neighbour interpolation for version 1.3 of GOME-2A LER climatology derived from Tilstra et al (2017), which is at a 1 • × 1 • grid. Typical values of the surface albedo over the region of interest is around 0.21.…”
Section: Demonstration Case: 2010 Russian Wildfiresmentioning
confidence: 99%
“…We use the exact illumination and viewing geometry (θ, θ 0 , ϕ − ϕ 0 ) of each individual measurement and colocate MODIS pixels with the GOME-2A pixel centre to obtain the surface BRDF parameters over the scene. For Lambertian cloud fractions, we use the GOME-2A surface LER value from Tilstra et al (2017). To simulate the measured reflectance, we assume the geometric 5 cloud fraction distribution shown in Fig.…”
Section: Gome-2a Cloud Fraction Simulationsmentioning
confidence: 99%
“…monthly 25 climatologies), a large ensemble of measurements taken over a scene over multiple years is analyzed statistically, and based on the lower 1% percentile reflectance, an inversion is done to retrieve the surface reflectance (e.g. Koelemeijer et al (2003), Kleipool et al (2008), Tilstra et al (2017)). Depending on the exact viewing and illumination geometry however, the surface may appear darker or brighter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation